1998
DOI: 10.1097/00004872-199816070-00009
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of cognitive status of old patients with isolated systolic hypertension

Abstract: In a cohort of elderly patients with isolated systolic hypertension, baseline cognitive function measured in terms of the MMSE score was high, probably due to selective recruitment of patients who were not clinically demented. Blood pressure was a weak contributor to cognitive status compared with age and level of education. Baseline cognitive function of women was negatively and independently correlated to systolic blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 40 publications
2
35
1
6
Order By: Relevance
“…However opinion remains divided, because of methodological issues including: (1) differences in the study populations (age, level of education, duration of hypertension, volunteers, referrals, or population samples) (2) differences in the neuropsychological tests used to evaluate the participants; and (3) the use of cross-sectional rather than longitudinal study designs. 79,80 Cross-sectional studies Many cross-sectional studies have attempted to determine whether cognitive function is related to hypertension. 79,[81][82][83][84][85][86][87][88][89][90][91] Cognitive function has been found to be negatively, positively or not associated with systolic blood pressure or diastolic blood pressure (Table 4).…”
Section: Hypertension and Cognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…However opinion remains divided, because of methodological issues including: (1) differences in the study populations (age, level of education, duration of hypertension, volunteers, referrals, or population samples) (2) differences in the neuropsychological tests used to evaluate the participants; and (3) the use of cross-sectional rather than longitudinal study designs. 79,80 Cross-sectional studies Many cross-sectional studies have attempted to determine whether cognitive function is related to hypertension. 79,[81][82][83][84][85][86][87][88][89][90][91] Cognitive function has been found to be negatively, positively or not associated with systolic blood pressure or diastolic blood pressure (Table 4).…”
Section: Hypertension and Cognitive Functionmentioning
confidence: 99%
“…79,80 Cross-sectional studies Many cross-sectional studies have attempted to determine whether cognitive function is related to hypertension. 79,[81][82][83][84][85][86][87][88][89][90][91] Cognitive function has been found to be negatively, positively or not associated with systolic blood pressure or diastolic blood pressure (Table 4). In the studies that demonstrated a significant positive correlation between cognitive impairment and hypertension, the neuropsychological domains predominantly affected were learning and memory, attention and mental flexibility.…”
Section: Hypertension and Cognitive Functionmentioning
confidence: 99%
“…Finally, the vascular dementia project, set up in the framework of the Syst-Eur trial, [30][31][32] investigated whether antihypertensive drug treatment could reduce the incidence of dementia. Compared with placebo (n = 1180), active treatment (n = 1238) reduced the rate of dementia by 50% from 7.7 to 3.7 cases per 1000 patient-years (21 vs 11 patients in the intention-to-treat analysis, P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A close association has also been shown between silent stroke (evidenced by cerebral white matter lesions) and echocardiographic LVH in 62 asymptomatic middle-aged patients with hypertension (Sierra, 2002). Many epidemiologic studies have indicated a correlation between blood pressure level and cognitive decline or dementia later in life (Starr, 1993;Seux, 1998;Postner, 2002;Hanon, 2003;Piguet, 2003;Whitmer, 2005). The importance of lowering blood pressure in hypertensive subjects is well-known, but the relationship between hypertension and cognitive function is still controversial.…”
Section: Hypertension-induced Brain Damagementioning
confidence: 99%